Estabilização de solo com adição de resíduo de mármore - Araújo, Meise Lopes (Universidade Federal Rural do Semi-Árido, 2018)
The pavement is formed by structural layers that must contain characteristics to support the loads coming from the traffic, in this way good quality materials are required to compose these layers. On the other hand, some regions of the country do not have adequate ground or close deposits to meet the constructive needs of the pavement. Therefore, an alternative to improve soil properties is your stabilization, which may be chemical, mechanical and granulometric. Thus, the present work aims to stabilize a soil from the Caraúbas/RN’s city with 2% of marble residue, in the normal, intermediate and modified compaction energies, in order to verify the viability of this soil for application in layers of pavements through the values obtained in the California Bearing Ratio (CBR), comparing the same with the parameters established by the DNIT for each pavement layer. This work consists of an experimental research. Plasticity Limit (LP), Liquidity Limit (LL), compaction and CBR tests were carried out at the Geotechnical Laboratory of the Universidade Federal Rural do Semi-Árido (UFERSA), Campus Caraúbas and Mossoró. Finally, the results show that as the compaction energy was increased, the soil support capacity was also increased. The soils under study can not be used in the base layer, since none had CBR equal to or greater than 80%. However the natural soil compacted in normal energy and stabilized with 2% compacted in the normal and intermediate energy, can be used in subgrade and subgrade reinforcement. However, the soil stabilized with 2% in the modified energy can be applied in the sub-base layer, since it presented CBR equal to 24.06%, that is, greater than 20%. It was also reported that the soil stabilized with 2% presented greater support capacity than the natural soil and the soil stabilized with 5%.
Monografia
Keywords: Estabilização; Resíduo de mármore; CBR; ENGENHARIAS::ENGENHARIA CIVIL